A Systematic Review on the Efficacy of Common Antacid Components - Gornez, Ma. Fatima Jesuniña M. (Animo Repository, 2021)
Gastroesophageal Reflux Disease (GERD) is a common health issue worldwide that utilizes antacids to mitigate its symptoms such as chest pains and burning sensations. However, the most common component used in antacids, Aluminum Hydroxide, has a high toxicity level as it builds up in the body. Thus, this study aims to determine whether Alginate, an organic compound, and Calcium Carbonate, which is considered an age-friendly component, are suitable antacid component alternatives to Aluminum Hydroxide in terms of their corresponding Acid Neutralization Capacity (ANC) and adverse effects. The researchers utilized a systematic review approach, guided by the Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols (PRISMA-P), to accomplish the study objectives. The study results suggest that Calcium Carbonate has the highest ANC while Alginate has the second-highest ANC and has fewer adverse effects than placebo. These results support the claim that Alginate and Calcium Carbonate are suitable alternatives to Aluminum Hydroxide.